Determining the digestible lysine requirement of Cobb MV × Cobb 500 FF broilers from 28-41 days of age and the effect of feeding varying digestible lysine levels on performance, processing, and economics - D.G. Dennehy; A.T. Brown; C. Coto; L. Mejia; K.G.S. Wamsley (Journal of Applied Poultry Research, 2023)
SUMMARY: The current objective was to expand on previous research using the Cobb MV × Cobb 500 to determine its finisher digestible Lys (dLys) requirement (Req; d 28–41), as well as the effect of feeding varying finisher dLys levels on performance, processing, and economics. This was a 2 Sex (male or female) × 8 dLys factorial arrangement, wherein the experimental diets consisted of a practical control; (PRAC-CON; 0.94% dLys) and 7 other diets with varying dLys concentrations (0.72%, 0.80%, 0.88%, 0.94%, 1.02%, 1.10%, and 1.18%) Chicks were fed common starter (1.28% dLys) and grower diets (grower 1 and 2 dLys were 1.18 and 1.08%, respectively). In general, males had improved performance versus females while females had increased processing yield (% of live weight) vs. males. Also, increasing finisher dLys resulted in improvements in performance and processing metrics, regardless of sex. Quadratic regression (QR; 95% of vertex) and linear and quadratic broken line (LBL; QBL) models were utilized to estimate dLys Req for each sex. The estimated dLys Req range for females was 0.752-1.292% and males, 0.748 to 1.320%, when using all models. An economic model determined 1.10% finisher dLys to be most profitable. These data demonstrate that increasing finisher dLys can improve Cobb MV × Cobb 500 performance and processing; however, the optimal dLys Req can vary depending on sex, regression model, response parameter, and economics.